ATHLETICS. INTRODUCTION OF INNOVATIVE TECHNOLOGIES IN MIDDLE DISTANCE RUNNING (CROSS SPORTS) - Nasirov Polatbay; Esemuratov Sultamurat (Bright Mind Publishing, 2025)
This paper examines the introduction of innovative technologies in athletics, with a special focus on middle-distance running, including cross-country. Modern technologies such as wearables, fitness trackers and data analysis software are significantly changing the way we approach training and competition. The use of GPS trackers allows athletes to optimize routes and track physical performance, which helps to increase the effectiveness of the training process. Virtual training and competitions open up new horizons for participants, allowing them to compete in conditions that were previously unavailable. In addition, health monitoring technologies play a key role in ensuring the safety of athletes. In conclusion, the importance of constantly updating the knowledge of coaches and athletes about modern technological solutions for achieving high results in athletics is emphasized.
Keywords: Athletics, middle-distance running, cross country, innovative technologies, fitness trackers, GPS trackers, virtual competitions.